PERANCANGAN MEDIA BRAND COMMUNICATION UNTUK MENINGKATKAN AWARENESS CAF… BABA SWITA - Nugraha, Aditia; Lukito, Wahyu; Mulya Prajana, Adya (Telkom University, 2024)
The phenomenon of the emergence of various cafes in Indonesia has become aneveryday sight. It can be seen from the many cafes that have sprung up from big cities to small towns, including the city of Bandung. Baba Swita is a new cafe in the city of Bandung.Baba Swita's advantages and potential are regularly communicated through only a few media platforms used, and it does not yet have maximum brand communication media,both online and offline, and wants to increase promotional efforts to further increase its awareness. To cover its target market widely, Baba Swita only consistently communicatesvia social media platforms in the form of Instagram. The phenomenon of the high level of the cafe industry and the rapid development of information media, Baba Swita needs tohave good brand communication in order to maintain and cover a wider market, namely by designing media and design systems and their application to communication media aspart of brand communication. This research was carried out by collecting data through literature study, observation, interviews and questionnaires which were then analyzedusing the SWOT analysis method, comparisonmatrix analysis, Consumer Insight and Consumer Journey. Keywords: design, brand communication, cafÈ, awareness, information development, media